Determination of Cocoa Powder Particle Size Distribution by Using the Buoyancy Weighing-Bar Method. Issue 1 (December 2020) - Tambun, R; Silalahi,; Hasibuan, R; Alexander, V
Abstract: This study aims to examine the determination of the particle size distribution of cocoa powder by using the Buoyancy Weighing-Bar Method (BWM) with ethanol as a liquid medium. Laser diffraction and settling balance method are used as a comparison method in this study. The weighing bar used in BWM consists of cylindrical aluminium with a size of 10 cm x 210 cm. The measurement process is operated at ambient temperature and the measurement is carried out for 180 minutes. The results obtained indicate that the particle size distribution of cocoa powder can be measured by using BWM, and the results obtained are proportional to the measurement results by using the settling balance method, while laser diffraction is not suitable for measuring cocoa powder particle size distribution due to the shape of the cocoa powder that is not a sphere.